Maastricht criteria III in the global context: a systematic review of development and implementation - Křivková, Jana; Šimek, Jiří; Lochmannová, Alena; Leden, Pavel (Nursing in the 21st Century, 2025)
Aim. This review examines the development and implementation of the Maastricht Criteria III in controlled (cDCD) and uncontrolled (uDCD) Donation after Circulatory Death in various healthcare systems, evaluates compliance with the no-touch interval, and the influence of opt-in versus opt-out consent models on the availability and use of donor organs. Material and methods. Following Evidence-Based Practice principles, a systematic search was performed in full-text electronic databases covering healthcare, bioethics, and transplantation sciences. Peer-reviewed, full-text studies relevant to DCD classification and clinical application were included. Additionally, a critical methodological quality appraisal of all included studies was conducted using a standardised tool, thereby enhancing the robustness of our conclusions. Results. Eleven studies met inclusion criteria, addressing DCD classification, consent frameworks, no-touch interval adherence, and organ procurement impact. Substantial international variability emerged: presumed consent (opt-out) systems achieved higher donor conversion rates, whereas extended no-touch intervals detrimentally affected organ viability. Conclusions. This review presents a structured analysis of Maastricht Criteria III application, particularly in Europe. cDCD follows increasingly standardised protocols, while uDCD remains inconsistently implemented due to ethical and logistical challenges. To enhance donor identification, organ utilisation, and transplantation outcomes, it is essential to standardise protocols, refine ischemia-mitigation techniques, and strengthen international collaboration.